Laves phase control of Inconel 718 alloy using quasi-continuous-wave laser additive manufacturing. (15th May 2017) - Xiao, Hui; Li, Simeng; Han, Xu; Mazumder, Jyoti; Song, Lijun
Abstract: Nb segregation and Laves phase formation are known to be detrimental to mechanical properties of Inconel 718. However, effective efforts to suppress Nb segregation and Laves phase formation are still lacking. In this work, a quasi-continuous-wave (QCW) laser additive manufacturing (LAM) is used to control Nb segregation and Laves phase formation. Thermal behaviors of the molten pool, microstructural evolution and mechanical response of the fabricated samples to aging treatment were investigated. Compared to continuous wave (CW) LAM, QCW-LAM results in a refined and equiaxed dendrite microstructure, a reduced Nb segregation, and attended fine and discrete Laves phase particles, due to an improved cooling rate with one order of magnitude and a decreased solidification time of the molten pool. In addition, the QCW sample shows a good response to aging treatment with a higher hardness and more desired tensile properties due to the reduced Nb segregation, the obtained fine discrete Laves phase and the refined dendrite microstructure. The tensile strength (~ 1404.1 MPa), the yield strength (~ 1120.6 MPa) and the ductility (~ 12.4 pct) of the aged QCW sample are higher than the ASTM limits of the wrought Inconel 718 alloy. Graphical abstract: Highlights: A quasi-continuous-wave laser additive manufacturing is used to control the Laves phase. The process features improved cooling rate and increased solidification rate. Refined equiaxed dendrites, reduced Nb segregation and scattered Laves phase are discussed. Good response to aging treatment with high mechanical properties is obtained.